2020
DOI: 10.1101/2020.02.07.939264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model-based analysis of polymorphisms in an enhancer reveals cis-regulatory mechanisms

Abstract: It is challenging to predict the impact of small genetic changes such as single nucleotide polymorphisms on gene expression, since mechanisms involved in gene regulation and their cis-regulatory encoding are not well-understood. Recent studies have attempted to predict the functional impact of non-coding variants based on available knowledge of cis-regulatory encoding, e.g., transcription factor (TF) motifs. In this work, we explore the relationship between regulatory variants and cis-regulatory encoding from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Although the mechanisms that we find are specific to the regulation of rhomboid and other neuroectodermal enhancers, and might not necessarily generalize to the regulation of other genes, our work gives a recipe for understanding the regulatory mechanisms in a data-driven or model-driven manner. In addition to their explanatory role, the models tested here can also be useful for predicting the expression driven by unseen sequences and cellular contexts; this ability has several applications in down-stream analysis such as predicting the effect of a particular TF’s knockout, site mutagenesis, or effects of single nucleotide polymorphisms on the expression ( 68 , 69 ). We also showed that convolutional neural networks can be a reliable expression prediction tool capable of learning non-linear regulatory mechanisms from modest-sized training data.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms that we find are specific to the regulation of rhomboid and other neuroectodermal enhancers, and might not necessarily generalize to the regulation of other genes, our work gives a recipe for understanding the regulatory mechanisms in a data-driven or model-driven manner. In addition to their explanatory role, the models tested here can also be useful for predicting the expression driven by unseen sequences and cellular contexts; this ability has several applications in down-stream analysis such as predicting the effect of a particular TF’s knockout, site mutagenesis, or effects of single nucleotide polymorphisms on the expression ( 68 , 69 ). We also showed that convolutional neural networks can be a reliable expression prediction tool capable of learning non-linear regulatory mechanisms from modest-sized training data.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms that we find are specific to the regulation of rhomboid and other neuroectodermal enhancers, and might not necessarily generalize to the regulation of other genes, our work gives a recipe for understanding the regulatory mechanisms in a data-driven or model-driven manner. In addition to their explanatory role, the models tested here can also be useful for predicting the expression driven by unseen sequences and cellular contexts; this ability has several applications in down-stream analysis such as predicting the effect of a particular TF’s knockout, site mutagenesis, or effects of single nucleotide polymorphisms on the expression (64, 65). We also showed that convolutional neural networks can be a reliable expression prediction tool capable of learning non-linear regulatory mechanisms from modest-sized training data.…”
Section: Discussionmentioning
confidence: 99%